2005
DOI: 10.1038/nature04247
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell engraftment at the endosteal niche is specified by the calcium-sensing receptor

Abstract: During mammalian ontogeny, haematopoietic stem cells (HSCs) translocate from the fetal liver to the bone marrow, where haematopoiesis occurs throughout adulthood. Unique features of bone that contribute to a microenvironmental niche for stem cells might include the known high concentration of calcium ions at the HSC-enriched endosteal surface. Cells respond to extracellular ionic calcium concentrations through the seven-transmembrane-spanning calcium-sensing receptor (CaR), which we identified as being express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
478
3
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 668 publications
(504 citation statements)
references
References 20 publications
14
478
3
9
Order By: Relevance
“…HSC status is believed to be controlled within the BM niche by orchestrated signaling circuits mediated by a variety of molecules including stem cell factor (SCF)/c-Kit, thrombopoietin (TPO)/c-Mpl, angiopoietin-1/Tie2, Wnt, Notch, bone morphogenic proteins, Ca 2þ , and chemokine (C-X-C motif) ligand 12 (or stromal-derived factor-1)/CXC receptor 4 (CXCR4) [2][3][4][5][6]. Also well documented is that cell-to-cell or cell-to-extracellular matrix interaction itself is crucial for the execution of HSC functions in the niche system [7]. In the setting of transplantation, HSCs must take several steps to achieve successful long-term engraftment, which include transendothelial migration into the BM cavity from circulation (homing), settling in the BM niche (lodging and retention), and intraniche proliferation and multilineage differentiation (repopulation).…”
Section: Introductionmentioning
confidence: 99%
“…HSC status is believed to be controlled within the BM niche by orchestrated signaling circuits mediated by a variety of molecules including stem cell factor (SCF)/c-Kit, thrombopoietin (TPO)/c-Mpl, angiopoietin-1/Tie2, Wnt, Notch, bone morphogenic proteins, Ca 2þ , and chemokine (C-X-C motif) ligand 12 (or stromal-derived factor-1)/CXC receptor 4 (CXCR4) [2][3][4][5][6]. Also well documented is that cell-to-cell or cell-to-extracellular matrix interaction itself is crucial for the execution of HSC functions in the niche system [7]. In the setting of transplantation, HSCs must take several steps to achieve successful long-term engraftment, which include transendothelial migration into the BM cavity from circulation (homing), settling in the BM niche (lodging and retention), and intraniche proliferation and multilineage differentiation (repopulation).…”
Section: Introductionmentioning
confidence: 99%
“…These CaRs detect and act upon subtle differences in calcium gradients and control the homing of HSCs to the appropriate stem cell niches. 170 At a macroscopic level, the hematopoietic system must respond to environmental stressors such as radiation, toxins (tobacco), medications, and industrial exposures, and these environmental factors directly impact the expression profile of normal hematopoietic cells. 5 Radiation exposure is one of the most extensively studied environmental exposures.…”
Section: Factors Impacting Hematopoietic Expressionmentioning
confidence: 99%
“…41,46 One of the key characteristics of the endosteal stem cell niche is the high extracellular calcium-ion concentration ([Ca 2 þ ]). 47 The HSCs express CaR, a G-protein-coupled receptor responding to the extracellular [Ca 2 þ ] level. Interestingly, a recent study showed that CaR-deficient mice had fewer HSCs in BM, and relatively more HSCs were found in the circulation and spleen.…”
Section: Self-renewal Of Hscsmentioning
confidence: 99%
“…CaR À/À FL HSCs are less effective at repopulating irradiated transplant recipients, and this deficit could be attributed to a defect in localization to the endosteal stem cell niche after transplantation. 47 It has been shown that a combination of signaling lymphocyte activation molecule (SLAM) expression defines long-term HSCs (CD150 þ CD48 À CD244 À ) from adult BM using FACS. 48 Because of its limited expression pattern, this combination of SLAMs can also be used in immunofluorescent imaging of LT-HSCs in tissue sections.…”
Section: Self-renewal Of Hscsmentioning
confidence: 99%